2018
DOI: 10.1021/acs.biomac.8b00497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anisotropy of Cellulose Nanocrystal Suspensions on Stratification, Domain Structure Formation, and Structural Colors

Abstract: Outstanding optical and mechanical properties can be obtained from hierarchical assemblies of nanoparticles. Herein, the formation of helically ordered, chiral nematic films obtained from aqueous suspensions of cellulose nanocrystals (CNCs) were studied as a function of the initial suspension state. Specifically, nanoparticle organization and the structural colors displayed by the resultant dry films were investigated as a function of the anisotropic volume fraction (AVF), which depended on the initial CNC con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 61 publications
1
75
0
Order By: Relevance
“…Further results from the characterization of the CNCs can be found in our previous study. 26 Milli-Q water (U.S.A. Millipore, Synergy UV) was used to dilute the CNC dispersion. Acetone was obtained from VWR Chemicals International S.A.S.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further results from the characterization of the CNCs can be found in our previous study. 26 Milli-Q water (U.S.A. Millipore, Synergy UV) was used to dilute the CNC dispersion. Acetone was obtained from VWR Chemicals International S.A.S.…”
Section: Methodsmentioning
confidence: 99%
“…24 A particularly appealing aspect of using highly anisotropic cellulosic building blocks is associated with their long-range order in aqueous dispersion or in the solid state. 21,25,26 Specically, it has been demonstrated that nematic ordering of CNCs and CNFs can greatly enhance the properties of the formed aerogels, for instance, enabling a high directional toughness while maintaining high optical transparency and thermal insulation. 21,27 Compared to conventional aerogels with isotropic skeletal structures, the porous assemblies of nematic ordered aerogels can be further enhanced by uniaxial compression, whereby pore size harmonization in expense of macropores and in favor of mesopores occurs.…”
Section: Introductionmentioning
confidence: 99%
“…They were received as a suspension at 11.1% solids concentration. Details about the CNCs are listed in previous work (Klockars et al 2018). Ethanol (A, 94%) was obtained from Altia Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The films in this study were all dried at 50% relative humidity to improve reproducibility, and to ensure a longer evaporation time and, therefore, to favor chiral nematic assembly as well as coffee ring formation via EISA (Klockars et al 2018;Tran et al 2018). Otherwise, at high enough drying rates, ''kinetic trapping or arrest'' would occur for particles, limiting the formation of the coffee ring (Li et al 2016).…”
Section: Coffee Ring Development In Square Filmsmentioning
confidence: 99%
See 1 more Smart Citation